Odpowiedzi

2010-04-15T12:05:49+02:00
2/×+1= -3/×-2 wynik ma być ( ×=1/5 )
zał: x≠-1 i x≠2

-3(x+1)=2(x-2)
-3x-3=2x-4
-5x=-1
x=1/5

3/×+1-2/×-1=4/×2 -1 wynik ma być ( ×= 9 )
zał: x≠-1 i x≠1

3/×+1-2/×-1=4/×2 -1 /*(×2 -1)
3(x-1)-2(x+1)=4
3x-3-2x-2=4
x-5=4
x=9
2010-04-15T12:10:03+02:00
2/(×+1)= -3/(×-2)
założenia
x+1≠0 i x-2≠0
x≠-1 i x≠2

wymnażam "na krzyż"
2(x-2)=-3(x+1)
2x-4=-3x-3
5x=1
x=⅕

b)3/(×+1)-2/(×-1)=4/(ײ -1)
założenia:
x+1≠0 i x-1≠0
x≠-1 i x≠1


ײ -1=(x+1)(x-1)
doprowadzam do wspólnego mianownika:

[3(x-1)-2(x+1)]/(ײ -1)=4/(ײ -1)
(3x-3-2x-2)/(ײ -1)=4/(ײ -1)
(x-5)/(ײ -1)=4/(ײ -1)
x-5=4
x=9